On the Convergence of Fourier Series with Orthogonal Polynomials inside and on the Closure of a Region - Abdullaev, F.G.; Küçükaslan, M. (Український математичний журнал, 2002)
We study the rate of convergence of Fourier series of orthogonal polynomials over an area inside and on the closure of regions of the complex plane. Досліджено швидкісіь збіжності рядів Фур'є ортогональних по площі поліномів всередині та на замиканні областей комплексної площини.